Koss's Cytology of the Urinary Tract with Histopathologic Correlations - Koss, MD, FCRP, Leopold G. (Springer New York : Imprint: Springer, 2012)
Fifteen years have elapsed since the publication of the original book under the same title.  With the passage of time little has changed and the same conceptual mistakes continue to be made in the practice of urinary cytopathology as in the past.  For this reason a much simplified new edition of this book with the application of new processing techniques has been thought to be a worthwhile undertaking .  Numerous new color photographs from the file of the co-editor have replaced old black and white photographs and will hopefully support the brief text for the benefit of patients. This volume will appeal to urologists as well as pathologists, cytopathologists and related professions.